NUEVOS HALLAZGOS DE GRAPTOLI1DS EN LA FORMACION SIERRA DE LA INVERNADA (ORDOVICICO), PRECORDILLERA DE SAN JUAN, ARGENTINA (Ameghiniana, 2013)
Recent geological investigations carried out in the Sierra de la Invernada. Central part of the Precordillera of San Juan, have allowed to recognize new graptolite occurrences. The fossils have been recorded in the Sierra de la Invemada Formation. The graptolite assemblage is referred to the Nemagraptus gracilis Zone.